TRANSFORMASI KOPERASI KONVENSIONAL MENUJU KOPERASI SYARIAH DI MAN KOTA SINGKAWANG - Luqman Luqman; Yulia Yulia; Lian Damero; Intan Purnama Sari; Hosaimah Hosaimah; Fitri Triastuti (Jurnal Inovasi dan Terapan Pengabdian Masyarakat, 2024)
Cooperative in Indonesia has a vital role in the national economy, especially in improving the welfare of members and society. MAN Kota Singkawang has a student cooperative called At-Ta'awun Cooperative. This cooperative was established initially as a conventional cooperative. However, the cooperative management saw that many members had different needs and preferences over time. Some members want a cooperative that is managed based on Islamic Sharia principles. The cooperative management intends to transform the At-Ta'awun Cooperative into a sharia cooperative. The method implemented in this service is seminars and discussions with the At-Ta'awun cooperative management with IAIN Pontianak. The result of this service is that the understanding of cooperative members regarding the concept of sharia cooperatives has increased rapidly. They now understand the fundamental differences between conventional and sharia cooperatives and the benefits and opportunities offered by sharia cooperatives.